WORK SUPERVISION POLICY COVID-19 EMERGENCY AGAINST THE EFFECTIVENESS OF EMPLOYEES HOTEL SUZUYA RANTAUPRAPAT - Halim, Abd.; Syamsuri, Abd. Rasyid (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2021)
As an effort and support the goverment’s appeal in handling and disconnecting the Covid-19 chain in community life, Suzuya Hotel Rantauprapat’s management participates in the adaptations of security and health procedures and protocols of the employess by evaluating the supervision of emergency work as well as in relation to work effectiveness. The results of this research can be explained that the role of company in suppressing the spread of Covid-19 in the workplace by conducting improved employee work organization. Management policy Suzuya Hotel Rantauprapat raises the security protocol through working supervision for each employee providing positive effect, easy delivery and appropriate variable indicators in measuring the work supervision and effectiveness of management work Suzuya Hotel Rantauprapat as part of the safety and health protocol of employee work during the Covid-19 emergencies running effectively and smoothly despite being in the green zone.